2018
DOI: 10.1093/biolre/ioy173
|View full text |Cite
|
Sign up to set email alerts
|

CBLB502, a Toll-like receptor 5 agonist, offers protection against radiation-induced male reproductive system damage in mice†

Abstract: CBLB502, a Toll-like receptor (TLR)5 agonist derived from Salmonella flagellin, was shown to protect mammalian hematopoietic and gastrointestinal systems from acute irradiation syndrome and to stimulate regeneration. To explore whether CBLB502 can improve testicular injuries caused by irradiation, mice were intraperitoneally injected with 0.2 mg/kg CBLB502 or vehicle control 30 min prior to applying 5.0 Gy ionizing radiation (IR). We observed these mice for the following 120 days and determined that CBLB502 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…In recent years, the protective roles of Toll‐like receptors (TLRs) have drawn more and more attention. The latest research showed that CBLB502, a TLR5 agonist derived from Salmonella flagellin , effectively protected mammalian haematopoietic and gastrointestinal systems from acute irradiation syndrome . Our previous studies have also proved that activation of TLR2 and TLR4 significantly protected mice and cultured cells against ionizing radiation.…”
Section: Introductionmentioning
confidence: 88%
“…In recent years, the protective roles of Toll‐like receptors (TLRs) have drawn more and more attention. The latest research showed that CBLB502, a TLR5 agonist derived from Salmonella flagellin , effectively protected mammalian haematopoietic and gastrointestinal systems from acute irradiation syndrome . Our previous studies have also proved that activation of TLR2 and TLR4 significantly protected mice and cultured cells against ionizing radiation.…”
Section: Introductionmentioning
confidence: 88%
“…Specifically, most altered miRNAs, lncRNAs, and mRNAs were either co-upregulated or co-downregulated (71, 3606, and 1051, respectively) between the CBLB502 and amifostine groups, with only a few showing opposite trends of change (1.39%, 0.36%, and 0.76%, respectively) ( Table 2). In contrast, although there were several co-regulated miRNAs, lncRNAs, and mRNAs between the amifostine and nilestriol groups (46,1107, and 591, respectively), higher percentages of altered RNAs were found in the opposite regulatory direction (9.80%, 16.45%, and 4.68%, respectively), indicating the different regulatory patterns between these 2 radioprotectants. Similarly, 14.89%, 17.44%, and 5.42% of the respective RNAs in the opposite regulatory direction showed different patterns between the CBLB502 and nilestriol groups (Table 2).…”
Section: Amifostine and Cblb502 Treatments Results In Similar Rna Profmentioning
confidence: 88%
“…Although the mechanisms of amifostine and CBLB502mediated radioprotection are poorly understood, 39 they are both likely to have a cytoprotective effect and rapid response against IR-induced stress within several hours, 5,40 with achieving complex radiation-cytoprotective effects by interfering with genes involved in scavenging free radicals, cell cycle regulation, apoptosis, and inflammation. 6,7,[41][42][43][44][45][46] However, nilestriol requires a longer time, usually hours or days, to exert its protective effects, and its post-irradiation mechanism does not involve primary radiation-induced cellular processes. 3,9 These differences in reaction time and mechanism may explain the similarities between amifostine and CBLB502 in terms of the influence on IR-induced RNAs, which was distinct from that of nilestriol.…”
Section: Discussionmentioning
confidence: 99%
“…CBLB502 was also stated to reestablish testicular antioxidant condition and decrease testicular oxidative injury caused by IR [ 66 ]. To evaluate if CBLB502 can reduce testicular damage, animals were intraperitoneally injected with CBLB502 prior to applying IR [ 67 ]. It was reported that CBLB502 administration reduced IR-provoked oxidative stress, decreased the alterations of architecture of seminiferous tubules, increased the sperm quality and quantity, and ameliorated male mouse fertility.…”
Section: Radioprotective Agentsmentioning
confidence: 99%
“…Furthermore, an IR-caused decrease in serum testosterone and superoxide dismutase (SOD) concentrations and an augmentation in malondialdehyde (MDA) concentrations were significantly inverted in CBLB502-pretreated animals. No relevant actions were reported in TLR5 knockout mice, proposing that defense of the testis against IR by CBLB502 is essentially due to the TLR5 signaling pathway [ 67 ].…”
Section: Radioprotective Agentsmentioning
confidence: 99%